Safety and Immunogenicity of the Respiratory Syncytial Virus Vaccine RSV/ΔNS2/Δ1313/I1314L in RSV-Seronegative Children. (12th October 2019) - Karron, Ruth A; Luongo, Cindy; Mateo, Jocelyn San; Wanionek, Kimberli; Collins, Peter L; Buchholz, Ursula J
Abstract: Background: Respiratory syncytial virus (RSV) is the leading global cause of severe pediatric acute respiratory tract illness, and a vaccine is needed. RSV/ΔNS2/Δ1313/I1314L contains 2 attenuating elements: (1) deletion of the interferon antagonist NS2 gene and (2) deletion of codon 1313 of the RSV polymerase gene and the stabilizing missense mutation I1314L. This live vaccine candidate was temperature-sensitive, genetically stable, replication restricted, and immunogenic in nonhuman primates. Methods: A single intranasal dose of RSV/ΔNS2/Δ1313/I1314L was evaluated in a double-blind, placebo-controlled trial (vaccine-placebo ratio, 2:1) at 10 6 plaque-forming units (PFU) in 15 RSV-seropositive children and at 10 5 and 10 6 PFU in 21 and 30 RSV-seronegative children, respectively. Results: In RSV-seronegative children, the 10 5 PFU dose was overattenuated, but the 10 6 PFU dose was well tolerated, infectious (RSV/ΔNS2/Δ1313/I1314L replication detected in 90% of vaccinees), and immunogenic (geometric mean serum RSV plaque-reduction neutralizing antibody titer, 1:64). After the RSV season, 9 of 20 vaccinees had increases in the RSV titer that were significantly greater than those in 8 of 10 placebo recipients (1:955 vs 1:69, respectively), indicating that the vaccine primed for anamnestic responses after natural RSV exposure. Conclusion: Rational design yielded a genetically stable candidate RSV vaccine that is attenuated yet immunogenic in RSV-seronegative children, warranting further evaluation. Clinical Trials Registration: NCT01893554. Abstract : A live attenuated respiratory syncytial virus (RSV) vaccine containing a deletion of the interferon antagonist NS2 gene and mutations in the polymerase gene was well tolerated and infectious, inducing primary neutralizing antibody responses and potent memory antibody responses in RSV-seronegative children.